Nurses' practice patterns in relation to adherence‐enhancing interventions in stem cell transplant care: a survey from the Nurses Group of the European Group for Blood and Marrow Transplantation. (7th January 2014) - Kirsch, M.; Berben, L.; Johansson, E.; Calza, S.; Eeltink, C.; Stringer, J.; Liptrott, S.; De Geest, S.
<x xml:space="preserve">Abstract</x> Recipients of stem cell transplants (SCT) must accurately manage multiple medications as non‐adherence jeopardises treatment benefits. There is an evidence base for the efficacy of adherence‐enhancing interventions; however, level of clinical implementation is unknown. This study aimed to identify patterns of practice in assessing medication adherence, screening for risk factors of non‐adherence, interventions used in SCT to improve adherence and how nurses perceive the effectiveness of such interventions. A convenience sample of 143 European nurses completed a 29‐item questionnaire measuring the frequency and perceived effectiveness of assessment/screening methods for adherence and three types of intervention (educational/cognitive, counselling/behavioural and psychological/affective). Questioning patients about adherence was the most regularly used assessment method (51.5%). Nurses used a median of seven interventions (interquartile range: six) 'frequently', the most popular being provision of reading materials (79%). The interventions perceived as most effective were; providing individual patient/family with teaching and reading materials. This is the first study exploring patterns of practice relating to adherence in SCT. Educational interventions were the most frequently employed style of intervention, which is at odds with recent data suggesting limited efficacy with this style of intervention. Combining educational, behavioural and psychological interventions would more accurately embrace current understanding.